Use of Supervisory Standards in the Financial Sector Assessment Program-Understandings with Standard Setting Bodies. (Policy Papers; Policy Paper ;, 2017)
This paper informs the Executive Board of the staff-level understandings reached with global Standard Setting Bodies (SSBs) on the use of the three financial sector supervisory standards in FSAPs: the Basel Committee's Core Principles for Effective Banking Supervision (BCP), set by the Basel Committee on Banking Supervision (BCBS); the Insurance Core Principles (ICP), set by the International Association of Insurance Supervisors (IAIS); and the Objectives and Principles of Securities Regulation (Principles), set by the International Organization of Securities Commissions (IOSCO). As graded assessments of compliance with supervisory standards are voluntary, FSAPs have adopted a flexible approach to the use of supervisory standards. A standard is either assessed in full, resulting in grades, or used as the basis for a deeper analysis of selected elements of the oversight framework in a focused review, without grades. The SSBs and Fund staff have reached understandings on a refinement of the existing flexible approach, with sets of 'base principles' serving as the starting points for focused reviews.